Evaluation of spur gear pair on tooth root bending stress in radial misalignment contact condition - Lias, M.R. (EDP Sciences, 2014)
This paper evaluates the effects of radial misalignment contact on the tooth root bending stress values of spur gear pair during the gear meshing cycle. Radial misalignment (H) is denoted as the deviation of the pinion nominal position with respect to the gear tooth along the pinion axis to the gear which happened from manufacturing assembly errors (AE). A model based on involute 3D parametric CAD geometry, of spur gear design ISO 6336:2006 is analysed with allowable AE values from minimum 10Î¼m to maximum 40Î¼m with Finite-Element Method (FEM) model based methodology using a dynamics module from ANSYS. Main parameters of interest are the Tooth root bending stress (TRBS) in H condition with AE along the critical region with respect to face width of pinion-gear section. A comparison between standard High point single tooth contact models (HPSTC) to this model showed a good agreement that H with AE had great influence on TRBS as the values' increase. Radial misalignment influence factor (RMIF) was introduced as indication of TRBS values in consideration of H due to AE shows and inverted patterns higher for pinion, give a good justification that the pinion is weaker compared to the gear. Â© 2014 Owned by the authors, published by EDP Sciences.